Trials and Tribulations: the Trial Tax and the Process of Punishment - Johnson, Brian (Crime and justice, 2019)
The jury trial has long been a keystone of the American criminal justice system. Few defendants exercise their right to trial, however, and those who do tend to receive significantly harsher punishments if convicted. This phenomenon, known as a trial tax or, conversely, as a guilty plea discount, is one of the most profound and consistent findings in the empirical sentencing literature. Estimates of its magnitude differ across studies and jurisdictions, but it typically involves a two- to six-times increase in the odds of imprisonment and a 15–60 percent increase in average sentence length. Recent changes to American sentencing policy may have exacerbated plea-trial disparities, raising a host of moral, legal, and procedural questions about fair and equal treatment of defendants who exercise their right to trial.